Serum magnesium, phosphorus, and calcium are associated with risk of incident heart failure: the Atherosclerosis Risk in Communities (ARIC) Study(1)(2)(3) - Lutsey, Pamela L (American Society for Nutrition, 2014)
Background: Heart failure (HF) is a major source of morbidity and mortality, particularly among the elderly. Magnesium, phosphorus, and calcium are micronutrients traditionally viewed in relation to bone health or chronic kidney disease. However, they also may be associated with risk of cardiovascular disease through a broad range of physiologic roles. Objective: With the use of data from the Atherosclerosis Risk in Communities (ARIC) cohort, we tested the hypotheses that the incidence of HF is greater among individuals with low serum magnesium and those with high serum phosphorus and calcium. Design: A total of 14,709 African Americans (27%) and whites from the ARIC cohort [aged 45–64 y at baseline (1987–1989)] were observed through 2009. Proportional hazards regression was used to explore associations between biomarkers and incident HF. Serum calcium was corrected for serum albumin. Models were adjusted for demographics, behaviors, and physiologic characteristics. Results: A total of 2250 incident HF events accrued over a median follow-up of 20.6 y. Participants in the lowest (≤1.4 mEq/L) compared with the highest (≥1.8 mEq/L) category of magnesium were at greater HF risk (HR: 1.71; 95% CI: 1.46, 1.99). For phosphorus, there appeared to be a threshold whereby only those in the highest quintile were at greater HF risk [HR((Q5 vs Q1)): 1.34; 95% CI: 1.16, 1.54]. Higher concentrations of calcium were also associated with greater risk of HF [HR((Q5 vs Q1)): 1.24; 95% CI: 1.07, 1.43]. Results were not modified by race, sex, or kidney function and were similar when incident coronary heart disease was included as a time-varying covariate. Conclusions: Low serum magnesium and high serum phosphorus and calcium were independently associated with greater risk of incident HF in this population-based cohort. Whether these biomarkers will be useful candidates for HF risk prediction or targets for prevention remains to be seen.